Accounts Receivable Accounting System at PT. Ahsan Farma Medika Banjarmasin - Ranti Permata Sari; Sirajudin; Hikmahwati (Magister Administrasi Bisnis ULM, 2025)
Abstract: PT Ahsan Farma Medika is a PBF (pharmaceutical wholesaler) engaged in the pharmaceutical sector which is a distributor of drug sales. This study aims to analyze and design a receivables accounting system at PT Ahsan Farma Medika Banjarmasin. This research uses qualitative research and uses a descriptive approach. The data sources used are primary data sources in the form of accounts receivable processes and procedures obtained from interviews, and secondary data in the form of a brief history, organizational structure, and documents related to the accounts receivable accounting system of PT Ahsan Farma Medika Banjarmasin. This research uses the interview method, documentation method and observation method to obtain the data. The results showed that PT Ahsan Farma Medika has not fully met the requirements of a good system. This can be seen from the absence of separation of functions, namely the credit function in charge of making decisions and the accounting function carried out by one person, then the accounting records and documents used have not implemented a sales return journal, general journal, cash receipt journal, credit memo, and memorial evidence. So, to meet the requirements of a good system, it is necessary to design an accounts receivable accounting system as an alternative to further optimize the accounts receivable accounting system. Keywords: Accounting System, Accounts Receivable, PT. Ahsan Farma Medika Banjarmasin